Nanoemulsions Based on Soluble Chenopodin/Alginate Complex for Colonic Delivery of Quercetin - Gamboa-Arancibia, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Inflammatory bowel disease (IBD) is an autoimmune disorder caused by uncontrolled immune activation and the subsequent destruction of the colon tissue. Quercetin (Qt) is a natural antioxidant and anti-inflammatory agent proposed as an alternative to mitigate IBD. However, its use is limited by its low oral bioavailability. This study aimed to develop nanoemulsions (NEs) based on a soluble chenopodin/alginate (QPA) complex and Tween 80 (T80), intended for the colonic release of Qt, activated by the pH (5.4) and bacteria present in the human colonic microbiota. NEs with different ratios of QPA/Tw80 (F1-F6) were prepared, where F4Qt (60/40) and F5Qt (70/30) showed sizes smaller than 260 nm, PDI < 0.27, and high encapsulation efficiency (>85%). The stability was evaluated under different conditions (time, temperature, pH, and NaCl). The DSC and FTIR analyses indicated hydrophobic and hydrogen bonding interactions between QPA and Qt. F4Qt and F5Qt showed the greater release of Qt in PBS1X and Krebs buffer at pH 5.4 (diseased condition), compared to the release at pH 7.4 (healthy condition) at 8 h of study. In the presence of E. coli and B. thetaiotaomicron, they triggered the more significant release of Qt (ƒ2 < 50) compared to the control (without bacteria). The NEs (without Qt) did not show cytotoxicity in HT-29 cells (cell viability > 80%) and increased the antioxidant capacity of encapsulated Qt. Therefore, these NEs are promising nanocarriers for the delivery of flavonoids to the colon to treat IBD. © 2024 by the authors.